2022
DOI: 10.1111/jocd.15047
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical lower eyelid rejuvenation using injectable poly‐d,l‐lactic acid in Asian patients

Abstract: Background Filler injection for lower eyelid rejuvenation remains a difficult subject due to many complicated anatomic changes as the face ages. Objectives To propose an alternative, simple, and effective filler injection method in lower eyelids for Asian patients. Methods Any patient who has tear trough deformities, infra‐orbital hollows, nasojugal grooves, dark eye circles, as well as mild eyebags is a potential candidate for this method. Our filler choice is injectable poly‐d,l‐lactic acid (PDLLA; AestheFil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Research performed by the manufacturer reported approximately 16,000 patients receiving facial injection of PDLLA filler from April 2014 to July 2018 with no serious adverse effects (i.e., death, blindness, and skin necrosis). Adverse side effects observed included mild swelling (50% of all patients), bruising (30%), and pain (20%) which were resolved or relieved with ice packing and medication [1]. Although previous studies showed safety of PDLLA as a subdermal filler, the present case had a major side effect of the multiple branch arterial occlusion after injection of PDLLA above the eyebrow.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Research performed by the manufacturer reported approximately 16,000 patients receiving facial injection of PDLLA filler from April 2014 to July 2018 with no serious adverse effects (i.e., death, blindness, and skin necrosis). Adverse side effects observed included mild swelling (50% of all patients), bruising (30%), and pain (20%) which were resolved or relieved with ice packing and medication [1]. Although previous studies showed safety of PDLLA as a subdermal filler, the present case had a major side effect of the multiple branch arterial occlusion after injection of PDLLA above the eyebrow.…”
Section: Discussionmentioning
confidence: 53%
“…Injectable poly-D, L-lactic acid (PDLLA) is a new cosmetic filler (AestheFill; REGEN Biotech, Inc., Seoul, South Korea). This subdermal stimulatory filler was first approved by the Korean Food and Drug Administration in 2014 and commercially marketed in Taiwan in 2020 [1]. Here, we presented the case of a 23-year-old female, who showed no previous ophthalmic medical history, complicated with sudden vision loss in the right eye after PDLLA injection at the glabella.…”
Section: Introductionmentioning
confidence: 99%
“…The eyelids and periorbital regions can be rejuvenated using a variety of medical and surgical procedures 23–25,30,31 . However, blepharoplasty is still the most popular 2,26–29 .…”
Section: Discussionmentioning
confidence: 99%
“…1 We proposed a simple and effective method using injectable poly-D,L-lactic acid (PDLLA; AestheFill; REGEN) recently in Journal of Cosmetic Dermatology. 2 The injection method is superficial, wide, and even distribution of PDLLA under eyes using fanning technique. 2 However, even distribution is difficult to achieve when performing traditional fanning technique especially for novice practitioners.…”
Section: Fan-dotting Injection Technique: a Simple Methods For Infrao...mentioning
confidence: 99%
“…For patients who have moderate-to-severe undereye defects, 3-4 ml of SWFI and 1 ml of lidocaine are used. 2 We choose a 1-cc syringe connecting with a 23G cannula as the injector. During injection, the whole cannula is inserted under the dermis from an entry point 1 cm lateral and inferior to the lateral canthus.…”
Section: Fan-dotting Injection Technique: a Simple Methods For Infrao...mentioning
confidence: 99%